Efficacy of the Motivational Interviewing–Walk Intervention for Chemotherapy-Induced Peripheral Neuropathy and Quality of Life During Oxaliplatin Treatment: A Pilot Randomized Controlled Trial. Issue 2 (March 2022) - Kanzawa-Lee, Grace A.; Ploutz-Snyder, Robert J.; Larson, Janet L.; Krauss, John C.; Resnicow, Kenneth; Lavoie Smith, Ellen M.
Abstract : Background: Oxaliplatin-induced peripheral neuropathy (OIPN) is prevalent among gastrointestinal cancer survivors and often impairs quality of life (QOL). Objective: This pilot randomized controlled trial aimed to explore the effect of an 8-week home-based brisk walking (the "MI-Walk") intervention on (1) OIPN severity and (2) QOL at 8 weeks, compared with physical activity (PA) education alone in oxaliplatin-receiving adults with gastrointestinal cancer. Interventions/Methods: Participants (N = 57) recruited from 5 infusion sites received PA education at their second oxaliplatin visit, followed by phone assessments of adverse events over 8 weeks. Half (n = 29) received additional MI-Walk intervention motivational supports (eg, a Fitbit Charge 2 and motivational enhancement therapy sessions). Self-reported OIPN, QOL, and PA were measured before and after intervention. Results: The intervention compared with the control condition had no effect on sensory OIPN (mean difference [(Equation is included in full-text article.)] = −0.01; P > .99), motor OIPN ((Equation is included in full-text article.)=2.39; P = .17), and QOL ((Equation is included in full-text article.)= −1.43; P > .99). Eight-week sensory ((Equation is included in full-text article.)=11.48 ± 0.38) and motor OIPN severities ((Equation is included in full-text article.) = 7.48 ± 0.36) were mild but higher than baseline ( P ⩽ .01). Self-reported PA level increased over time in both groups ((Equation is included in full-text article.)=44.85; P = .01). Averaging ≥225 moderate to vigorous PA minutes per week led to less sensory OIPN, particularly finger/hand tingling ((Equation is included in full-text article.)= −26.35; P = .01). Conclusions: This study failed to detect beneficial effects of the MI-Walk intervention; however, the findings suggest that aerobic walking may blunt but not completely prevent OIPN. Further research is necessary. Implications for Practice: Although the effectiveness of brisk walking in reducing OIPN is unclear, this study supports prior evidence that moderate to vigorous PA is beneficial and safe during chemotherapy treatment.